Sphingomonas paeninsulae sp. nov., isolated from soil sampled at Fildes Peninsula, Antarctica. Issue 12 (31st October 2019) - Geng, Yingchao; Zhang, Yumin; Qin, Kun; Liu, Jia; Tian, Jin; Huang, Yao; Wei, Ziyan; Zhang, Fang; Peng, Fang
Abstract : Strain YZ-8 T, isolated from soil sampled at Fildes Peninsula, Antarctica, was found to be a Gram-stain-negative, yellow-pigmented, oxidase- and catalase-positive, non-motile, non-spore-forming, rod-shaped and aerobic bacterium. Strain YZ-8 T grewoptimally at pH 7.0 and 20 °C. Tolerance to NaCl was up to 0.3 % (w/v) with optimum growth in the absence of NaCl. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain YZ-8 T belonged to the family Sphingomonas . Strain YZ-8 T showed the highest sequence similarities to Sphingomonas molluscorum KMM 3882 T (94.4 %), Sphingomonas oligophenolica JCM 12082 T (94.4 %), Sphingomonas gotjawalisoli SN6-9 T (94.3 %) and Sphingomonas aquatica W1-2-1 T (94.3 %). The predominant respiratory isoprenoid quinone and polyamine components were identified as ubiquinone Q-10 and sym -homospermidine, respectively. In addition, carotenoid were also found. The polar lipid profile of the strain YZ-8 T was found to contain one phosphatidylethanolamine, an unidentified phospholipid, one diphosphatidylglycerol, one phosphatidylglycerol, two sphingophosphonolipids, one phosphatidylcholine and two unidentified alkali-stable lipids. The G+C content of the genomic DNA was determined to be 58.8 mol%. The main fatty acids were summed feature 8 (comprising C18 : 1 ω7 c and/or C18 : 1 ω6 c ; 35.4 %), summed feature 3 (comprising C16 : 1 ω7 c and/or C16 : 1 ω6 c ; 32.6 %) and C14 : 0 2-OH (7.7 %). On the basis of the evidence presented in this study, a novel species of the genus Sphingomonas, Sphingomonas paeninsulae sp. nov., is proposed, with the type strain YZ-8 T (=CCTCC AB 2017137 T =LMG 31027 T ).